Pengaruh Penambahan Limbah Karbit Terhadap Stabilisasi Tanah Daerah Rawa - Ikhsan Nur Amarullah; Muhammad Zardi (Jurnal Teknik Sipil Unaya, 2019)
This study aims to determine the effect of the addition of carbide waste as a stabilizing material to the value of the CBR (California Bearing Ratio) and peat soil direct shear. The land used came from Lueng Gayo Village. The CBR value increased from 1.63% in the original soil to 17.09% in a mixture of 15% carbide waste, this is caused because the elements contained in carbide waste such as silica (SiO2) and calcium oxide (CaO) which act to fill the pore empty pores. The value of the shear angle (φ) has increased from 20.24o in the original soil to 29.02o in the mixture of carbide waste, this is caused by chemical reactions that occur due to mixing of chemical elements, especially (Ca) contained in the carbide waste. The cohesion value (c) has decreased from 0.12 kg / cm2 in the original soil to 0.09 kg / cm2 in the carbide waste mixture. This is caused by the reaction of carbide waste which is absorbing water, causing inter-particle decline. The value of the shear strength increased 0.22 kg / cm2 at the addition of 5% carbide waste, then decreased 0.17 kg / cm2 at the addition of 10% and increased 0.29 kg / cm2 at the addition of 15% carbide waste. This is due to chemical reactions that occur due to mixing of chemical elements contained in carbide waste